The Mediating Role of Customer Trust in the Effect of Service Quality and Customer Perceived Value on Customer Satisfaction - Dewi, Maya Kumala; Praswati, Aflit Nuryulia (Jurnal Ilmiah Manajemen Kesatuan, 2024)
With the continued development of the beauty industry, there has been a real increase in the number of beauty producers and clinics spread throughout Indonesia. This research aims to analyze the influence of service quality and customer perceived value on customer satisfaction which is mediated by trust in beauty clinic users. With a sample size of 100 respondents. After the data was collected, it was analyzed using SmartPLS3.0 software. This research is a type of descriptive quantitative research which aims to provide a further description of the symptoms or phenomena that occur. This is a type of correlation research, which means knowing how the independent variable and dependent variable correlate with each other. The results that can be revealed in this research are that the variable service quality has a significant positive effect on customer satisfaction, service quality has a significant positive effect on trust, customer perceived value has a significant positive effect on customer satisfaction, customer perceived value has a positive and significant effect on trust, trust has a positive effect and significant on customer satisfaction, trust has a negative and insignificant effect mediating service quality on customer satisfaction, trust has a positive and significant effect mediating customer perceived value on customer satisfaction.